(untitled) (Baghdad Science Journal, 2011)
Samples of Oxytricha falax were collected from Tigris River by 55µ. mesh net. Culturing of O. falax were cultivated in specific conditions (DO 3-5mg/l.; W.Temp. 24±1ºC; pH: 6.8-7.5).The effect of various furfural concentration 0, 20, 40, 80,100 and 124 ppm and toluene concentration 0, 15, 30, 34.2, 34.5 and 35 ppm after two periods of treatment (24 and 48 hr.) on the physiological parameters of O. falax ciliate were observed. This study showed that the lethal concentration of furfural was 124ppm and 80ppm after 24hr. and 48hr. from treatment which killed all the individual community respectively. Furthermore the treatment of O. falax individuals with different concentrations of toluene indicated that 34.5 ppm of it caused disappearance of the individuals’ population after 48hr., while the 35ppm concentration from toluene caused dead of all individuals after 24 hr. from their treatment.